(untitled) (Swiss Medical Weekly, 2014)
In the coming decades, old patients will account for an increasing proportion of emergency department (ED) visits. During or after their stay in the ED, they more frequently suffer adverse outcomes than younger patients. There is evidence that specific age-centred approaches improve the outcomes. We therefore reviewed specific conditions needing particular attention in older ED patients, such as cognitive disorders and delirium, impaired mobility and falls, as well as problems related to the activities of daily living, disability, poly-pharmacy, adverse drug effects, co-morbidity and atypical presentation. We also propose steps to further improve the quality of care in older ED patients by using appropriate age-centred management.